Sublime Rock: Burmese Popular Music, Language Code Switching and Sentimentalism among Shan Migrants at The Thai-Burma Border - Jane M Ferguson (Wacana Seni Journal of Arts Discourse, 2012)
While economic strife and internal conflict continue to drive migrants and refugees across the border from Burma into Thailand, one often uncounted aspect of this migration is that of the Burmese media texts and popular culture artifacts consumed by ethnic nationalities in exile. While many theorists of popular media and cultural studies alike have tended to look at the ways in which historically underrepresented groups might take their own renditions of popular musical forms and create symbolic acts of resistance, how, then can we understand people's relationships to dominant forms? Does the appreciation of a dominant form of popular culture necessarily imply subscription to dominant ideology? If popular music can be proven to be a mechanism for the creation of identity and place, what, then does it mean that Shan nationalists still listen to certain Burmese popular songs? Using ethnographic data gathered in a Shan community at the Thai-Burma border between 2004 and 2005, this article will provide an overview of the various ways in which popular culture texts circulate in the borderlands, and also the ways in which Burmese popular music is subjectively understood by members of one ethnic nationality community.